Performance optimization in redox flow batteries: a computational approach - Pilonetto, Luis Felipe (2022)
Redox flow batteries (RFBs) emerge as an alternative technology for the storage of energy on a large scale. The main characteristics of this type of device are related to its unique design, which provides scalability, decoupling between power and energy density, and the use of several types of active species. The more developed RFB to date is the all-vanadium redox flow battery (VRFB), which uses V2+/V3+ in one half-cell and VO2+(V(IV))/VO2+/(V(V)) in the other. Despite the advantages of this type of device, the VRFB still faces some drawbacks related to performance, which hinder its marketing penetration. Two of the most relevant problems are capacity loss and voltage loss. The capacity loss is caused by the non-ideal selectivity of the membrane, which allows the cross-contamination between the half-cells, leading to self-discharge reactions. The voltage loss is caused by overpotential that requires higher charging voltages and decreases the output voltage. Based on these problems, we propose a new computational method of approach to investigate the variables related to these problems and to suggest mitigation strategies to be further tested in real systems. Beyond the problems related to VRFBs, we also investigate the consequences of choosing different actives species in the performance of RFBs, based on this same method of approach. With this approach, we: (i) show how geometry influences the mitigation of overpotential and how geometric parameters interact with operating conditions; (ii) identify the operating conditions that affect the capacity loss and purpose a mitigation strategy based on the volume transfer between tanks in the reverse direction of net cross-contamination; and (iii) provide useful insights to understand how the choice of active species in RFBs is relevant to energy efficiency. Thus, we provide a set of theoretical backgrounds for experimentalists to understand the effects of several variables in the performance of redox flow batteries.